Penerapan Model Pembelajaran Kooperatif Tipe Round Table untuk Meningkatkan Hasil Belajar Tematik Siswa Sekolah Dasar - Fitri, Elia; Nasution, Minto Ito; Rejeki, Rejeki (Edusia: Jurnal Ilmiah Pendidikan Asia, 2022)
This study aims to find out the application of the round table cooperative learning model to improve thematic learning outcomes of the students in class V of state elementary schools 002 Rambah Samo. The background of this research is that the non-achievement of the learning objectives is reflected in the daily test scores of students in thematic learning and inactivity in the learning process. Of the 21 students, only nine achieved the KKM score, while 12 did remedial, and the KKM was set at 75. The subjects receiving the action in this study were students of class V, odd semester of state elementary school 002 Rambah Samo in the 2021/2022 academic year, as many as 21 students. Consists of 9 male students and 12 female students. The data analysis technique used is the model of collecting several instruments in the form of student question sheets. The results of this study were seen from the first cycle of the first meeting with 12 students, 57% of whom reached the KKM. In cycle one, the second meeting also increased again, with as many as 14 people, 67%. In the first two cycles of action, learning outcomes increased from 21 students to 17 (81%) students who had reached the  KKM. At the second meeting, there were satisfactory results from 21 students, 19 (90%) of whom achieved the KKM. This study concludes that applying the round table type cooperative learning model to improve thematic learning outcomes of the fifth-grade students of the state elementary school 002 Rambah Samo was successful.